mRNA encoding bone morphogenetic protein-2 facilitated peri-implant bone formation of titanium implants placed in rat femurs - Kanoksiri Jriyasetapong; Nopparada Lawtrakulngam; Philaiporn Vivatbutsiri; Sunporn Namano; Kamolporn Wattanasirmkit; Somphote Angkhanawiriyarak; Jaijam Suwanwela (Scientific Reports)
Abstract This study evaluated the effectiveness of N1-methylpseudouridine-modified mRNA encoding bone morphogenetic protein-2 (BMP-2 mRNA-LNP) in promoting bone growth and improving titanium implant integration in rat femur bone defects. Sixteen Sprague-Dawley rats (32 femurs) were used, with titanium wires implanted in the femoral defects. The defects were divided into four groups (n = 8): 5 µg BMP-2 mRNA-LNP, 15 µg BMP-2 mRNA-LNP, recombinant BMP-2 (rhBMP-2), and Dulbecco’s phosphate-buffered saline (dPBS). Following euthanasia at 3 and 6 weeks, Micro-Computed Tomography (micro-CT) was performed to assess bone volume, trabecular architecture, and bone-to-implant contact. Push-out mechanical testing determined the maximal loading force for implant dislodgment, while elemental analysis using Energy-Dispersive X-ray Spectroscopy (EDS) and Scanning Electron Microscopy (SEM) assessed mineralization on the titanium surfaces. The 15 µg BMP-2 mRNA-LNP group demonstrated significantly enhanced bone volume, trabecular thickness, and bone-to-implant contact compared to the control group (p < 0.05). Additionally, this group showed higher calcium and phosphorus content, indicating superior mineralization. Concomitantly, the mean maximal loading force (N) increased in the BMP-2 mRNA-LNP group, though this increase was not statistically significant. These results suggest that BMP-2 mRNA-LNP offers a promising approach to enhance peri-implant bone formation and bone regeneration. While the 15 µg group showed slightly greater bone formation, most experimental parameters showed no significant differences compared to the 5 µg group, suggesting the lower dose may offer a more cost-effective approach without compromising efficacy.